Ag‐ZnO Nanocomposite Thin Film by RF‐Sputtering: An Electrical and Structural Study. Issue 1 (18th December 2017) - Singh, S. K.; Singhal, R.; Siva Kumar, V. V.
Abstract : In the present study, pure ZnO and Ag‐ZnO nanocomposite (NCs) thin films with three different compositions were grown by RF magnetron co‐sputtering technique at substrate temperature 300 °C. The composite nature of the thin films was confirmed by Rutherford backscattering spectroscopy (RBS) and showed the existence of Ag, Zn, and O. The Ag fraction was found to be 8 at.%, 15  at.%, and 40 at.% in ZnO matrix. X‐ray diffraction analysis of the pure and composite thin films confirms the formation and structure of the film and reveal the hexagonal wurtzite structure of the pure ZnO thin film. Structural modifications in pure and composite thin films were observed by scanning electron microscopy (SEM). Raman measurements of the pure and Ag‐ZnO nanocomposite thin film were performed for the estimation of lattice defect and disordering which were induced by Ag incorporation. Electrical measurements revealed that the conductivity of nanocomposite thin film enhance drastically as compared to pure ZnO film and it increases with increasing Ag concentration. Furthermore, nanocomposite thin films showed a p‐type conductivity due to the incorporation of Ag metal, confirmed by Hall measurements.